1999
DOI: 10.1177/15910199990050s143
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Histopathology of Intracranial Aneurysms after Endovascular Treatment with Coils

Abstract: We describe the results of electron microscopic examination in two patients with ruptured intracranial aneurysms who were successfully treated by endovascular coil embolization. The aneurysms were seen completely occluded on the follow-up angiograms. Autopsies of these patients were performed five and 26 months after endovascular treatment when they died of pneumonia and thalamic hemorrhage, respectively. The aneurysms were densely filled with the coils, which were readily identified through the thin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Three to twelve months following embolization, there is increased vascularized connective tissue within the aneurysm dome and about the coils. Continued foreign body reaction with multinucleated giant cells is seen about the aneurysm coils 17, 23, 25 . One case report demonstrated that the neck is completely covered by a layer of long slender cells resembling endothelium during this time period (Figure 1e) 17 .…”
Section: Histopathological Mechanism Of Aneurysm Healing Following Bamentioning
confidence: 97%
See 1 more Smart Citation
“…Three to twelve months following embolization, there is increased vascularized connective tissue within the aneurysm dome and about the coils. Continued foreign body reaction with multinucleated giant cells is seen about the aneurysm coils 17, 23, 25 . One case report demonstrated that the neck is completely covered by a layer of long slender cells resembling endothelium during this time period (Figure 1e) 17 .…”
Section: Histopathological Mechanism Of Aneurysm Healing Following Bamentioning
confidence: 97%
“…Swine models of aneurysm healing demonstrate robust neointima formation with a thick layer of vascular smooth muscle cells and robust deposition of endothelial cells 4, 33 . Endothelial cells are primarily seen growing along the coils at the aneurysm neck which has led some investigators to believe that the endothelial cells arise from the adjacent vessel wall 18, 25 . However, recent studies suggest that endothelial cells found at the aneurysm neck may originate from bone marrow derived endothelial progenitor cells rather than migration of adjacent endothelial cells 34, 35 .…”
Section: Histologic Findings In Animal Models Following Bare Platinummentioning
confidence: 99%